Decision processes in German mutual fund companies: Evidence from a telephone survey - Kerstin Drachter; Alexander Kempf; Michael Wagner (University of Cologne, Centre for Financial Research (CFR), 2006)
The performance of actively managed mutual funds is largely dependent upon the investment decisions of the responsible fund managers. However, little is known about the behavior of these managers. This survey study sheds light on the decision processes of German fund managers. The design of the survey allows us to link fund manager data with information about mutual funds and fund management companies. This synthesis results in improved understanding of the mutual fund management decision process. The evidence shows that (i) it is possible to conduct a high quality survey study even though managers know that their answers will be linked to their performance and (ii) the behavior of managers depends heavily on the characteristics of the funds and the characteristics of the fund company.
Keywords: 330; Mutual funds; fund managers; decision process; survey study